2017
DOI: 10.1097/gox.0000000000001222
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and Histologic Examination after Subcutaneous Injection of Two Volumizing Hyaluronic Acid Fillers: A Preliminary Study

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Accordingly, these fillers may be more appropriate for the correction of NLFs (Pierre, Liew, & Bernardin, ). Previous studies of monophasic fillers found that the B filler was more cohesive and better maintained over time than the J filler (Micheels et al, ). In their study, the present authors found that in terms of 3D changes in facial height, the B filler was superior to the Y filler.…”
Section: Discussionmentioning
confidence: 94%
“…Accordingly, these fillers may be more appropriate for the correction of NLFs (Pierre, Liew, & Bernardin, ). Previous studies of monophasic fillers found that the B filler was more cohesive and better maintained over time than the J filler (Micheels et al, ). In their study, the present authors found that in terms of 3D changes in facial height, the B filler was superior to the Y filler.…”
Section: Discussionmentioning
confidence: 94%
“…When the HA gel goes out of the needle, it is distributed into the skin tissues depending on the rheological properties and cohesivity of the gel and the specific physico-mechanical properties of the receiving tissues [4,13] . The cohesivity, defined as the capacity of a material not to dissociate, because of the affinity of its molecules for each other, is naturally important during the product distribution into the tissues of the treated area [7] .…”
Section: Discussionmentioning
confidence: 99%
“… 28 Nevertheless, application of 3D-MR is restricted to the preclinical animal model, being more laborious and invasive with respect to US technique. 29 …”
Section: Discussionmentioning
confidence: 99%